(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
Solid-state fermentation (SSF) is an alternative low cost useful process that has many important applications in the field of biotechnology. In this study, SSF has been employed as a process for the production of value-added agricultural by-product using coconut testa (CT), rice bran (RB) and the combination of both substrates (CT-RB). The effect of SSF by Monascus purpureus on total phenolic content (TPC), antioxidant, anti-tyrosinase and anti-elastase of the substrates were studied and compared with its non-fermented counterparts. The results showed that the SSF has improved the TPC up to three-fold higher in the studied substrates. Antioxidant potential evaluated using FRAP analysis also exhibited an enhancement in fermented substrates with the values ranging from 23.70 to 63.15 mg AAE/g sample. On the other hand, the radical scavenging activity evaluated using DPPH assay showed a different trend in comparison to the TPC and FRAP analyses. In another two analyses, tyrosinase and elastase inhibition activities were also enhanced in most substrates upon the fermentation. The changes in free phenolic acids content (p-coumaric, caffeic, ferulic, sinapic, vanillic, protocatechuic, gallic and 4-hydroxybenzoic and syringic acid) of the substrates after fungal fermentation was also examined through high performance liquid chromatography (HPLC) analysis. In summary, SSF offers a tool to further increase the bioactive potential of the studied substrate.